REGULATORY FUNDAMENTALS FOR IMPLEMENTATION OF INFORMATION TECHNOLOGY PROJECTS IN INDUSTRY - L. V. Gubich; M. Y. Kovalyov; N. P. Mukcha; G. P. Matiushenko (Informatika)
The article provides an overview of the existing regulatory basis for the development of IIST. The features of IT projects management and a brief description of methodological recommendations on implementation of IT projects of the State scientific and technical Program «Electronic enterprise resource planning (CALS-ERP-technology)» for 2011–2015 are considered.